2017
DOI: 10.1136/thoraxjnl-2017-210770
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement of diameter and volume measurements for pulmonary nodule size estimation in CT lung cancer screening

Abstract: Pre-results, ISRCTN63545820.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 7 publications
1
44
1
1
Order By: Relevance
“…Nodule volumetry provides a more accurate assessment for baseline size and subsequent growth than diameter measurements. 12 Nodule volume is the preferred method for evaluation in the BTS guidelines and recommended as a more accurate method in the latest Fleischner Society guideline. 13 It appears in several diagnostic algorithms but is insufficient in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Nodule volumetry provides a more accurate assessment for baseline size and subsequent growth than diameter measurements. 12 Nodule volume is the preferred method for evaluation in the BTS guidelines and recommended as a more accurate method in the latest Fleischner Society guideline. 13 It appears in several diagnostic algorithms but is insufficient in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also looked at semantic features, proposing that pulmonary nodules with a larger diameter, located in the upper lobe, spiculation, and PSN (part-solid nodule) had a higher probability to be malignant [27]. However, it has been shown that semi-automated volume analysis is a more robust method than a simple measurement of the diameter to measure the size of the pulmonary nodule [28], and spiculation is an uncommon feature in early-stage lung cancer [8]. Our study finds that nodule diameter and nodule type are significantly different between cohorts diagnosed with IA and PM, with nodules with smaller diameter and pure GGN types increasing the probability of PM diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the NELSON trial, nodule growth was defined as a change in the volume of at least 25% between two subsequent examinations based on validation studies with repeated low-dose CT examinations performed on the same days, in which the measurement error was maximally 25% (3). However, optimization of the VDT cutoff for fast-growing nodules in lung cancer screening revealed that lowering the VDT cutoff could reduce false-positive referrals (28). D Not all CT screening facilities can use the software that was used in the NELSON trial.…”
Section: Discussionmentioning
confidence: 99%